TGFβ shuts the door on T cells - Bald, Tobias (Br J Cancer, 2018)
T cell exclusion from cancers is a major problem for a proportion of patients suffering poor outcomes. Two papers recently published in Nature highlight the negative role of cancer associated fibroblast TGFβ. These studies indicate that TGFβ enables T cell exclusion in a proportion of colorectal and urothelial cancers, and in the latter disease may reduce their response to anti-PD-L1 immunotherapy.